2019
DOI: 10.1080/09168451.2018.1562873
|View full text |Cite
|
Sign up to set email alerts
|

Soy sauce increased the oxidative stress tolerance of nematode via p38 MAPK pathway

Abstract: Soy sauce – a fermented food made from soybeans and wheat – is considered a healthy seasoning, but little scientific evidence is available to support this. In this study, physiological effects of soy sauce were analyzed using Caenorhabditis elegans. When soy sauce was fed to C. elegans together with Escherichia coli OP50, fat accumulation decreased, and resistance to oxidative stress by H2O2 was greatly increased in the nematodes. qRT-PCR revealed that mRNA expression of oxidative stress tolerance genes, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…MAPKs have significant roles in mediating signals triggered by cytokines, growth factors, and environmental stress; and are involved in controlling cell proliferation, cell differentiation, and death [73,74]. Recently, it has been reported that soy sauce induced mitochromesis and increased oxidative stress tolerance, which is mediated through p38 MAPK pathway [75]. Development and progression of breast tumors involve a complex series of events, including oxidative stress, dysregulation of cellular differentiation, excessive proliferation and resistance to apoptosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs have significant roles in mediating signals triggered by cytokines, growth factors, and environmental stress; and are involved in controlling cell proliferation, cell differentiation, and death [73,74]. Recently, it has been reported that soy sauce induced mitochromesis and increased oxidative stress tolerance, which is mediated through p38 MAPK pathway [75]. Development and progression of breast tumors involve a complex series of events, including oxidative stress, dysregulation of cellular differentiation, excessive proliferation and resistance to apoptosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…Other than just a seasoning, soy sauce is also a potential functional food with anti-obesity and anti-hypertensive effects. In previous studies, soy sauce intake was found to alter the fat metabolism of Caenorhabditis elegans [18]. Traditional Korean soy sauce can ameliorate hypertension in rats [19].…”
Section: Introductionmentioning
confidence: 94%